Building lecturers’ innovation recognised in 4th International Innovation, Design and Articulation (i-IDeA™) Perlis / Nor Azizah Talkis - Talkis, Nor Azizah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
The team’s innovation project entitled ‘3D Visual Model for Building Quantities Take-off (3D-ViMO)' is a teaching and learning aid for building quantity course. Students are expected to utilize it by downloading the 3D visual model which consists of every building element involved in the building quantity course. This 3D-ViMO can facilitate them in visualizing the building elements that need to be quantified. In line with the emergence of the Industrial Revolution (IR) 4.0, the methods of teaching embrace the latest learning and teaching tech-nologies. Hence, 3D-ViMO was proposed to replace the traditional method of learning with a more interactive approach involving 3D visual model and cooperative learning.